Who's afraid of euro area monetary tightening? CESEE shouldn't - André Geis; Isabella Moder; Tobias Schuler (European Central Bank (ECB), 2020)
After a first phasing out of the ECB's net asset purchases at end-2018, the question of how a future tightening of the ECB's monetary policy may affect countries located in the vicinity of the euro area has gained prominence, but has been left largely unanswered so far. Our paper aims to close this gap for the CESEE region by employing shock-specific conditional forecasts, a methodology that has been little exploited in this context. Besides demonstrating the usefulness of our framework, we obtain three key findings characterising the spillovers of ECB monetary policy to CESEE economies: first, a euro area monetary tightening does trigger sizeable spillovers to the CESEE region. Second, we show that in the context of a demand shock-induced monetary tightening, which is more realistic than the usual approach taken in the literature, CESEE countries' output and prices actually respond positively. Third, spillovers on output and prices in CESEE countries are heterogeneous, and depend on the trajectory of euro area tightening.
Keywords: C11; C32; E52; F42; 330; Monetary policy; international shock transmission; BVAR; EU integration